A Proposed Method for Age Detection of Person Based on the size of Face to the size of the Eye of a Face - et. al., Payal Bose, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Age Detection scheme is to estimate and predict the real age or age group of a person. Facial expressions, emotions, posture, illumination, hair style and aging can be determined from facial appearance. A person at the age of 20 and at the age of 80 can never be identical in respect of facial expression. The structure of face is an important factor in determining age of a person. In this paper age detection technique has been presented with an aim to detect age of a person.